Liability Of The Lessee Who Pledges The Leased Object In A Lease Agreement At Transtour And Travel Jogja - Sholihah, Ulinnuha Putri Yuwan; Heriyani, Endang (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Disputes in car rental agreements arise when renters pawn rented vehicles to third parties without the owner's consent, resulting in a breach of contract. To analyze this issue, the study used a legal-empirical method with a qualitative descriptive approach through the collection of primary data from interviews and secondary data from legal literature and relevant legislation. The problem was solved by assessing the lessee's legal responsibility and reviewing the dispute resolution mechanism used. The results of the study show that the act of pawning a rental car constitutes a breach of contract because it violates the obligations of use and return of the rental object, thereby giving rise to the lessee's responsibility to return the vehicle, pay the outstanding rent, and compensate for the damage. In addition, dispute resolution is carried out through non-litigation means, namely deliberation, which results in a compensation agreement without going to court.